Keys in the minoritised language teaching. An approach to the case of Aragonese language - Campos Bandrés, Iris Orosia (Didáctica. Lengua y Literatura, 2019)
The Aragonese language is one of the regional languages of Aragon. This language has been historically minoritised until the present day. Nevertheless, it has been two decades since its first introduction in the Infant Education and the Primary Education. However, there is very little research focused on the development of Aragonose teaching-learning process and also on its current situation at school. With the aim of contributing to the field of Aragonese teaching, and also to the field of minoritised languages didactics’, we implemented a qualitative research under the diary study. The contributions from the 32 participating children have shown the very little competence achived by students thanks to an obsolete system implemented. Moreover, we confirm the emergence of an affective factor and a diglossic conception of Aragonese that determinate the lingüístic representations of children. In any case, the evaluation of the didactic proposals developed by teachers is considerabily positive. We find also the reiterated demand for a greater space for the Aragonese language teaching at the school.